The Fabric of Empire : Material and Literary Cultures of the Global Atlantic, 1650-1850 - Skeehan, Danielle C., 1980- (Book collections on Project MUSE., 2020)
"This book combines material history with literary interpretation in a richly theoretical work of cultural history. The author examines the global textile trade alongside early Atlantic printing and papermaking and considers how these two related media were fundamental to the social fabrication of Atlantic subjects and Creole societies"--